Analysis of Factors Related to the Event of Diarrhea in Toddlers in the Wae Kajong - dervina sesandri aryani; Sony Doke; Daniela L.A Boeky (Lontar : Journal of Community Health, 2023)
Diarrhea is a condition in which the frequency of bowel movements in infants or children is more than three times a day, accompanied by changes in the consistency of the stool to liquid with or without mucus and blood that lasts less than seven days, taking place suddenly.This study aimed to analyze the relationship between exclusive breastfeeding, nutritional intake, and mother’s habit of washing hands with soap with the incidence of diarrhea. The research design is a cross-sectional study held from September-October 2021. The independent variables are exclusive breastfeeding, toddler nutrition, and the mother's habit of washing hands with soap. while the dependent variable is the incidence of diarrhea in toddlers. The research sample was 60 respondents considered by sampling technique using simple random sampling of 328 mothers with toddlers. The data collection method was conducted by interview using a questionnaire and analyzed by chi-square test. The results showed that there was a relationship between exclusive breastfeeding and the incidence of diarrhea (p = 0.001 <0.05); there is a relationship between nutrition of children under five with the incidence of diarrhea in children under five (p = 0.000 <0.05); there is a relationship between infection factors and the incidence of diarrhea in children under five (p = 0.000 <0.05); and there is a relationship between the mother's habit of washing hands with soap (p=0.000 <0.05) with the incidence of diarrhea in children under five in the Work Area of ​​the Wae Kajong Public Health Center, Manggarai Regency.